Outcomes of Bone Marrow Mononuclear Cell Transplantation for Neurological Sequelae Due to Intracranial Hemorrhage Incidence in the Neonatal Period: Report of Four Cases - Nguyen Thanh Liem; Truong Linh Huyen; Le Thu Huong; Ngo Van Doan; Bui Viet Anh; Nguyen Thi Phuong Anh; Dang Thanh Tung (Frontiers Media S.A., 2020)
Aim: The aim of this study was to present primary outcomes of autologous bone marrow mononuclear cell (BMMNC) transplantation to improve neurological sequelae in four children with intracranial hemorrhage (ICH) incidence during the neonatal period.Methods: GMFM88 and modified Ashworth score were used to assess motor function and muscle spasticity before BMMNC transplantation and after transplantation. Brain MRI was performed to evaluate brain morphology before and after BMMNC transplantation. Bone marrow were harvested from anterior iliac crest puncture and BMMNCs were isolated using Ficoll gradient centrifugation. The microbiological testing, cell counting, and hematopoietic stem cell (hHSC CD34+ cell) analysis were performed, following which BMMNCs were infused intrathecally.Results: Improvement in motor function was observed in all patients after transplantation. In addition, muscle spasticity was reduced in all four patients.Conclusion: Autologous BMMNC transplantation may improve motor function and reduce muscle spasticity in children with ICH incidence during the neonatal period.